2016
DOI: 10.2196/jmir.5580
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Decision-Making Based on Review Websites: Are There Differences Between Choosing a Hotel and Choosing a Physician?

Abstract: BackgroundWeb users are increasingly encouraged to rate and review consumer services (eg, hotels, restaurants) and, more recently, this is also the case for physicians and medical services. The resemblance in the setup and design of commercial rating websites (CRWs) and Web-based physician rating websites (PRWs) raises the question of whether choice-making processes based on the two types of websites could also be similar.ObjectiveThis qualitative study sought to explore the extent to which consumer decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
(46 reference statements)
2
32
0
2
Order By: Relevance
“…However, it is also useful to consider the reasons why participants’ awareness and usage of PRWs were all significantly lower in comparison with the other non–health care-related rating websites, which is consistent with the results of the 2 Hanauer et al studies [ 21 , 22 ]. In a recently published study by Rothenfluh et al, the choice-making processes of participants using the rating website TripAdvisor to select a hotel and the PRW Jameda to select a physician were explored [ 33 ]. Despite involving 2 service goods, major differences between the uses of the 2 rating websites were found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is also useful to consider the reasons why participants’ awareness and usage of PRWs were all significantly lower in comparison with the other non–health care-related rating websites, which is consistent with the results of the 2 Hanauer et al studies [ 21 , 22 ]. In a recently published study by Rothenfluh et al, the choice-making processes of participants using the rating website TripAdvisor to select a hotel and the PRW Jameda to select a physician were explored [ 33 ]. Despite involving 2 service goods, major differences between the uses of the 2 rating websites were found.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although participants felt confident in evaluating the quality of a hotel, they perceived that they had an inability to properly evaluate the skills and abilities of physicians. Finally, participants reported that interpersonal connection, gut feeling, and likeability played a huge role in selecting a physician, whereas the price and offered facilities were more important in relation to hotels [ 33 ]. Drawing from the economics literature, Rothenfluh et al distinguished between different types of services goods according to the level of information asymmetry between the provider and consumer and consequently suggested that these 2 service goods (hotels and physicians) cannot be treated equally because of their unequal attributes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been a steady increase in research into OPF websites, with studies conducted in the UK [9,11,13,14,16--24], Germany [ 16 - 21 ], Netherlands [ 22 ], Australia [ 23 ] and other countries [ 24 , 25 ] all contributing to the OPF evidence basis. Some evidence can be found to suggest that there is an association between online ratings and the quality of care [ 12 , 13 , 26 - 28 ], but the results are often conflicting [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of a nationally representative sample of the U.S. population, Hanauer et al also asked participants to consider the implications of leaving negative comments about a physician; participants reported being concerned that their identity could be disclosed, and that the physicians may take action against them for leaving negative comments [ 17 ]. Finally, recent studies by Rothenfluh et al indicate that a number of patients perceive that they have an inability to properly evaluate the skills and abilities of physicians [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%